2020
DOI: 10.3390/ma13225192
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Thermo-Chemical Treatments Methods of Ti-6Al-4V Alloy in Terms of Tribological and Corrosion Properties

Abstract: Titanium and its alloys are characterized by high mechanical strength, good corrosion resistance, high biocompatibility and relatively low Young’s modulus. For many years, one of the most commonly used and described titanium alloys has been Ti-6Al-4V. The great interest in this two-phase titanium alloy is due to the broad possibilities of shaping its mechanical and physico-chemical properties using modern surface engineering techniques. The high coefficient of friction and tendency to galling are the most impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…Numerous physical and chemical surface modifications can and have been applied to metallic biomaterials in general [11], specifically to titanium-based materials [12], and most recently to the application of nano-modifications [13]. This has led to the invention of many new types of titanium-based orthopedic materials with not only a higher resistance to corrosion and better tribological properties [14,15], but also improved mechanical properties [16][17][18][19]. In addition, biocompatibility [19] and resistance to bacterial infections [12,[20][21][22] can be positively influenced by those newly developed materials.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous physical and chemical surface modifications can and have been applied to metallic biomaterials in general [11], specifically to titanium-based materials [12], and most recently to the application of nano-modifications [13]. This has led to the invention of many new types of titanium-based orthopedic materials with not only a higher resistance to corrosion and better tribological properties [14,15], but also improved mechanical properties [16][17][18][19]. In addition, biocompatibility [19] and resistance to bacterial infections [12,[20][21][22] can be positively influenced by those newly developed materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, Al, Cr, Ti, and V are also used in some surface treatment methods. The most commonly used thermochemical surface treatments are carburizing, nitriding, carbonitriding, nitrocarburizing and boriding [35].…”
Section: Thermochemical Surface Treatmentsmentioning
confidence: 99%
“…[9,10] These modification methods form very hard ceramic surfaces exhibiting high wear, corrosion and oxidation resistance, chemical stability, and biocompatibility. [11,12] It has been reported that coating titanium with TiC also significantly improves osseointegration through improved bone growth compared to uncoated titanium. [13,14] Moreover, capping of different substrates by a thin TiC layer provids a longer lifetime for the implants in the body.…”
Section: Introductionmentioning
confidence: 99%